ANALISIS NILAI TAMBAH DAN PEMASARAN SUSU SAPI PADA USAHA SAPI PERAH DI KECAMATAN SELUPU REJANG KABUPATEN REJANG LEBONG - Sugiarti, Sri; Sriyoto, .; Gusfarina, Defira Suci (Badan Penerbitan Fakultas Pertanian, Universitas Bengkulu, 2007)
The object of this study are : 1) to know the scale of the added value of milking-cow manufacture becomes pasteurize milk and ginger milk instant, 2) to know the kind of marketing channel and margin distribution of milking-cow in Selupu Rejang, Rejang Lebong, Bengkulu Province. This study was done since July until August 2006.The location of this study was determined purposively. The respondents of this study were 23 milking-cow breeder, two collectors in marketing position and two manufacturers. The analysis method of this study is descriptive for general illustration of the location and the kind of marketing channel. Hayami’s method was use to analyze quantitative for the added value, margin distribution was counted by the using the cost in the breeders level and the price in the consument’s level